2015
DOI: 10.1016/j.actamat.2014.10.056
|View full text |Cite
|
Sign up to set email alerts
|

From heterogeneous to homogeneous nucleation for precipitation in austenite of microalloyed steels

Abstract: This paper studies the influence of strain on precipitate nucleation in austenite for three is dependent not only on the strain magnitude but also on the driving force for precipitation. When the driving force is high, or low in absolute terms, the influence of the strain, i.e. the increase in the dislocation density, gives rise to a notable reduction in the t 0.05 value due to heterogeneous nucleation on the dislocation nodes. In contrast, when the driving force is low, or high in absolute terms, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…found that in shock-compressed SiO 2 , silica transforms into a form of glass which subsequently exhibits ultrafast crystallization within nanoseconds. Mediana32 also reported that the nucleation time of precipitates is only 0.05 s when the strain and driving force for phase transformation are high. In the present study, nanoscale precipitates can nucleate and grow during the early cooling stage.…”
Section: Discussionmentioning
confidence: 98%
“…found that in shock-compressed SiO 2 , silica transforms into a form of glass which subsequently exhibits ultrafast crystallization within nanoseconds. Mediana32 also reported that the nucleation time of precipitates is only 0.05 s when the strain and driving force for phase transformation are high. In the present study, nanoscale precipitates can nucleate and grow during the early cooling stage.…”
Section: Discussionmentioning
confidence: 98%
“…On the basis of the crystal growth theory, the crystal nuclei tend to attach themselves on the already existed phases in order to reduce the energy for their growth (heterogeneous nucleation [30]). In this case, the undissolved TiN will act as the basement for the TiC growth in the molten pool, as Fig.…”
Section: Sem Analysismentioning
confidence: 99%
“…3). [36] which shows that the influence of the strain on the incubation time depends on the microalloying content, whereby the influence exerted is greater, the lower the microalloying content. In other words, when the driving force for nucleation of precipitates (ΔG v ) is high, or low in absolute terms, the strain as a promoter of the increase in the dislocation density exerts an important influence on the incubation time.…”
Section: Dn Dn Dt Dtmentioning
confidence: 90%
“…(4) at the nose temperature (T N = 1228 K; 955°C) was -1.554 × 10 9 J -3 . According to Medina et al [19,36] the incubation time corresponding to 5% of the precipitated volume t 0.05 , which in practical terms can be taken as the nucleation period for precipitation, depends on the strain as follows:…”
Section: Dn Dn Dt Dtmentioning
confidence: 99%